The Relationship Between Family Support and Depression Levels in Patients with Pulmonary Tuberculosis - Hadisaputri, Muliawati Supono; Sriyati; Istiqomah (Advances in Healthcare Research, 2025)
Purpose: Tuberculosis (TB) not only affects physical health but also impacts patients' psychological well-being, particularly in the form of depressive disorders. Family support is believed to play a crucial role in helping reduce these depressive levels. This study aims to analyze the relationship between the level of family support and the severity of depression in patients with pulmonary tuberculosis. Research Method: This study employed a quantitative approach with a descriptive, correlational, cross-sectional design. A total of 30 pulmonary TB patients at Respira Lung Hospital participated in the survey through a total sampling approach. Data were collected using a family support questionnaire and the Beck Depression Inventory-II (BDI-II), then analyzed using the Chi-Square test with a significance level of 0.05. Results and Discussion: The results indicate that patients with good family support were less likely to experience moderate or severe depression. Conversely, all patients with low-income family support experienced depression at various levels. The Chi-Square test showed a significant relationship between family support and depression levels (ρ = 0.000). Implications: This study confirms that family support plays a crucial role in maintaining the mental health of patients with pulmonary tuberculosis. Family involvement should be integrated into nursing interventions to enhance treatment outcomes and improve the psychological well-being of patients.